Enhanced sonodynamic therapy by carbon dots-shelled microbubbles with focused ultrasound - Ching-Hsiang Fan; Nan Wu; Chih-Kuang Yeh (Ultrasonics Sonochemistry, 2023)
Sonodynamic therapy involving the non-invasive and local generation of lethal reactive oxygen species (ROS) via ultrasound (US) with sonosensitizers has been proposed as an emerging tumor therapy strategy. However, such therapy is usually associated with inertial cavitation and unnecessary damage to healthy tissue because current sonosensitizers have insufficient sensitivity to US. Here, we report the use of a new proposed sonosensitizer, carbon dots (C-dots), to assemble microbubbles with a gas core (C-dots MBs). As the C-dots were directly integrated into the MB shell, they could effectively absorb the energy of inertial cavitation and transfer it to ROS. Our results revealed the appearance of 1O2, •OH, and H2O2 after US irradiation of C-dots MBs. In in vitro experiments, treatment with C-dots MBs plus US induced lipid peroxidation, elevation of intracellular ROS, and apoptosis in 32.5%, 45.3%, and 50.1% of cells respectively. In an animal solid tumor model, treatment with C-dots MBs plus US resulted in a 3-fold and 2.5-fold increase in the proportion of ROS-damaged cells and apoptotic cells, respectively, compared to C-dots MBs alone. These results will pave the way for the design of novel multifunctional sonosensitizers for SDT tumor therapy.